birds; Chiapas; Central Plateau; Zinacantán; habitat use; vertical distribution; - Altamirano González Ortega, Marco A.; González, José E. (Instituto de Ecología, A.C., 1998)
A vertical stratification analysis of the avifauna in an area ot 16 ha. known as San José Bocomtenelte, Zinacantán, Chiapas, México, is presentad. Seventy-six species of birds were recorded from february to december 1 993. Based on presance-absence data of birds in tha vegetation layers, we obtained a vertical distribution on four levels, their species' composition and the relationships to the foliage density. Results suggest that an inverse relation exist between vertical distribution of the avifauna and an increase in foliage density, originated mainly for specific-morphologic factors of birds and the vegetation structure, being these and the avaliability of food, the determinant factors that define bird distribution.